In-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode and its preparation method and application

By self-assembling ZIF-67 on nickel foam and preparing composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrodes by hydrothermal method, the problem of insufficient stability and conductivity of Ni-Co LDH electrode materials was solved, and high specific capacitance and stability improvement were achieved.

CN114121505BActive Publication Date: 2025-04-29HUBEI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111421442.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-26
Publication Date
2025-04-29
Estimated Expiration
2041-11-26

AI Technical Summary

Technical Problem

The existing nickel-cobalt double hydroxide (Ni-Co LDH) electrode materials have large volume changes during charging/discharging, resulting in poor stability, insufficient conductivity, and poor stability of artificial composite interfaces, affecting actual application performance.

Method used

The sheet-like ZIF-67 was self-assembled in situ on nickel foam by room temperature impregnation method, and then the hydrothermal method was used to obtain the in situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide (Ni-Co LDH) nanosheet array electrode to improve conductivity and stability.

Benefits of technology

The high specific capacitance, stability and conductivity are achieved, the stacking and agglomeration of Ni-Co LDH is avoided, the load capacity is increased, and the process is low, environmentally friendly and non-toxic, and there is no need to add binder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114121505B_ABST
    Figure CN114121505B_ABST
Patent Text Reader

Abstract

The present invention provides an in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode and its preparation method and application, belonging to the field of electrode material technology. In the present invention, the nickel foam substrate acts as a conductive grid to promote electron transfer, and the prepared electrode allows nitrogen-doped carbon to be self-compounded in the Ni‑CoLDH matrix. The excellent conductivity of nitrogen-doped carbon can promote the charge transfer of the electrode during energy storage. The self-generated composite material has the characteristics of uniform symbiosis, interface stability, and enhanced conductivity; the in-situ grown Ni‑CoLDH nanosheet array not only inherits the sheet structure, porous characteristics and stability of ZIF‑67, but also has excellent hydrophilicity, and a large number of sheet-like Ni‑CoLDH are also grown on the nanosheet array structure, effectively avoiding the problems of stacking, agglomeration and low load of Ni‑CoLDH.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to an in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode, and a preparation method and application thereof. Background Art

[0002] In recent years, the demand for energy has continued to grow with the consumption of fossil energy and the increase in population. The development and utilization of clean energy has been increasingly valued by many countries, and intermittent energy storage is also crucial. Supercapacitors have become the best choice for high-power applications, such as aerospace, automobiles, and military, due to their ultra-high power density, excellent rate performance, and outstanding cyclability. Currently, commercial supercapacitors are double-layer capacitors based on carbon materials, but their low energy density greatly limits their application. This carbon-based double-layer material achieves physical energy storage through the adsorption and desorption of ions on the surface of electrodes and electrolytes. Compared with traditional double-layer capacitor materials, pseudocapacitor supercapacitors exhibit higher energy density, which comes from the Faraday redox reaction between pseudocapacitor materials and electrolyte ions.

[0003] Nickel cobalt double hydroxide (Ni-Co LDH) is a pseudocapacitive material with an ultra-high theoretical specific capacitance. However, the large volume change of the two-dimensional structure of Ni-Co LDH during the charge / discharge process leads to poor stability, and its own poor conductivity and easy stacking and agglomeration make it difficult for the material to reach the theoretical capacitance value in practical applications. Therefore, many scholars hope to improve the conductivity of Ni-Co LDH by combining materials with good conductivity as reinforcing phases with the Ni-Co LDH matrix. However, the artificial composite method has poor interface stability, uneven distribution of phases inside the electrode material, easy stacking and agglomeration, and the need for additional adhesives, resulting in poor effects on improving the conductivity and stability of Ni-Co LDH. Summary of the invention

[0004] In view of this, the object of the present invention is to provide an in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode and its preparation method and application. The present invention in-situ self-assembles sheet ZIF-67 on nickel foam by room temperature impregnation method, and then obtains in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide (Ni-Co LDH) nanosheet array electrode by hydrothermal method, which has high specific capacitance, and the electrode stability and conductivity are also improved.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing an in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode, comprising the following steps:

[0007] Mixing cobalt nitrate, 2-methylimidazole and water to obtain a mixed solution;

[0008] The nickel foam is immersed in the mixed solution, sealed and allowed to stand, and then washed and dried in sequence to obtain a ZIF-67@Ni foam electrode;

[0009] mixing cobalt nitrate, nickel nitrate, hexamethylenetetramine and water to obtain a metal precursor solution;

[0010] The ZIF-67@Ni foam is placed in the metal precursor solution for hydrothermal reaction to obtain the in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode.

[0011] Preferably, the cobalt nitrate in the mixed solution is added in the form of cobalt nitrate hexahydrate, and the mass ratio of the nickel foam, cobalt nitrate hexahydrate, 2-methylimidazole and water in the mixed solution is 0.7-1:5-8:11-14:70-90.

[0012] Preferably, the drying temperature is 50-70°C.

[0013] Preferably, the cobalt nitrate and nickel nitrate in the metal precursor solution are added in the form of cobalt nitrate hexahydrate and nickel nitrate hexahydrate, and the mass ratio of cobalt nitrate hexahydrate, nickel nitrate hexahydrate, hexamethylenetetramine and water in the metal precursor solution is 0.2-0.4:0.7-1.2:1-1.3:30-50.

[0014] Preferably, the temperature of the hydrothermal reaction is 80-100° C., and the time is 0.5-3 h.

[0015] Preferably, the nickel foam further includes pretreatment before use, and the pretreatment is a first water washing, acetone washing, a second water washing, a hydrochloric acid washing, a third water washing, an ethanol washing, and drying performed in sequence. The first water washing time is 10 to 20 minutes, the acetone washing time is 10 to 20 minutes, the second water washing time is 10 to 20 minutes, the hydrochloric acid washing time is 5 to 15 minutes, the third water washing time is 10 to 20 minutes, and the ethanol washing time is 10 to 20 minutes.

[0016] Preferably, the drying temperature is 50-70° C. and the drying time is 10-20 hours.

[0017] Preferably, the cleaning comprises water washing, ethanol soaking and water washing in sequence, and the ethanol soaking time is 5 to 10 minutes.

[0018] Preferably, the sealing is left to stand for 4 to 10 hours.

[0019] The present invention also provides a self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode prepared by the preparation method described in the above technical solution.

[0020] The present invention also provides the application of the self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode described in the above technical solution in a supercapacitor.

[0021] The invention provides a preparation method of an in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode. The method comprises the following steps: mixing cobalt nitrate, 2-methylimidazole and water to obtain a mixed solution; immersing nickel foam in the mixed solution, sealing and standing the solution, and then sequentially washing and drying the solution to obtain a ZIF-67@Ni foam electrode; mixing cobalt nitrate, nickel nitrate, hexamethylenetetramine and water to obtain a metal precursor solution; placing the ZIF-67@Ni foam into the metal precursor solution for hydrothermal reaction to obtain the in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode. The present invention prepares an electrode by compounding nitrogen-doped carbon with good conductivity and Ni-Co LDH with high theoretical capacity, and designs an electrode preparation method for spontaneously compounding nitrogen-doped carbon with Ni-Co LDH by using flaky cobalt-based metal organic framework ZIF-67 and Ni-Co LDH, wherein ZIF-67 is formed by chemical bonding of cobalt ions and organic ligands, and cobalt ions are combined with hydroxyls through a simple hydrothermal step to in-situ form Ni-Co LDH, while the organic ligands are derived into nitrogen-doped carbon that is spontaneously compounded in Ni-CoLDH.

[0022] Beneficial effects:

[0023] (1) In situ self-assembly of electrode materials on nickel foam, the nickel foam substrate with good conductivity acts as a conductive grid to promote electron transport;

[0024] (2) Compared with the traditional rhombic dodecahedral ZIF-67, the sheet-like ZIF-67 nanosheets are easier to self-assemble on the substrate in situ. The electrode material is not easy to fall off during use. The actual contact area between the electrode and the electrolyte is larger, and the conductivity is better.

[0025] (3) The cobalt ions in ZIF-67 combine with hydroxyl groups to form Ni-Co LDH in situ, while the organic ligands are derived into nitrogen-doped carbon and self-compounded in Ni-Co LDH;

[0026] (4) The nitrogen-doped carbon nanosheet arrays grown by the hydrothermal method not only inherit the sheet structure, porous characteristics and stability of ZIF-67, but also have excellent hydrophilicity;

[0027] (5) A large amount of flaky Ni-Co LDH was also grown on the nanosheet array structure, which effectively avoided the stacking and agglomeration problems of powdered Ni-Co LDH and increased the Ni-Co LDH loading capacity;

[0028] (6) Nitrogen-doped carbon has good electrical conductivity. Combining it with Ni-Co LDH can improve the conductivity of the material and promote charge transfer of the electrode during energy storage;

[0029] (7) The process of the present invention is low in cost, environmentally friendly and non-toxic. No binder needs to be added during the preparation of the electrode, and the electrode can be directly used as an electrode, which can be extended to the practical application of supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a scanning electron microscope image of the in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode prepared in Example 2;

[0031] Figure 2 This is a Fourier infrared absorption spectrum of the in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode prepared in Example 2;

[0032] Figure 3 Cyclic voltammetry curves of nickel-cobalt double hydroxide nanosheet array electrode materials prepared in Examples 1 to 4;

[0033] Figure 4 The cyclic voltammetry curve of the topological electrode material prepared in Example 2;

[0034] Figure 5 This is a constant current charge and discharge curve diagram of the topological electrode material prepared in Example 2. DETAILED DESCRIPTION

[0035] The present invention provides a method for preparing an in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode, comprising the following steps:

[0036] Mixing cobalt nitrate, 2-methylimidazole and water to obtain a mixed solution;

[0037] The nickel foam is immersed in the mixed solution, sealed and allowed to stand, and then washed and dried in sequence to obtain a ZIF-67@Ni foam electrode;

[0038] mixing cobalt nitrate, nickel nitrate, hexamethylenetetramine and water to obtain a metal precursor solution;

[0039] The ZIF-67@Ni foam is placed in the metal precursor solution for hydrothermal reaction to obtain the in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode.

[0040] The invention mixes cobalt nitrate, 2-methylimidazole and water to obtain a mixed solution.

[0041] In the present invention, the cobalt nitrate in the mixed solution is preferably added in the form of cobalt nitrate hexahydrate, and the mass ratio of the foamed nickel, cobalt nitrate hexahydrate, 2-methylimidazole and water in the mixed solution is preferably 0.7-1:5-8:11-14:70-90.

[0042] In the present invention, the water is preferably deionized water.

[0043] The present invention preferably weighs 1-2 g of cobalt nitrate hexahydrate into a beaker, then adds 60-100 mL of deionized water and stirs fully to make the solution clear and transparent to obtain a cobalt nitrate solution; weighs 1-5 g of 2-methylimidazole into a beaker, then adds 60-100 mL of deionized water and stirs fully to make the solution clear and transparent to obtain a 2-methylimidazole solution, and then pours the cobalt nitrate solution into the 2-methylimidazole solution.

[0044] After obtaining the mixed solution, the present invention immerses the nickel foam in the mixed solution, seals the solution, and then sequentially washes and dries the solution to obtain a ZIF-67@Ni foam electrode.

[0045] In the present invention, the nickel foam preferably further includes pretreatment before use, and the pretreatment is preferably a first water washing, acetone washing, second water washing, hydrochloric acid washing, third water washing, ethanol washing, and drying performed in sequence, the first water washing time is preferably 10 to 20 minutes, the acetone washing time is preferably 10 to 20 minutes, the second water washing time is preferably 10 to 20 minutes, the hydrochloric acid washing time is preferably 5 to 15 minutes, the third water washing time is preferably 10 to 20 minutes, and the ethanol washing time is preferably 10 to 20 minutes. In the present invention, the hydrochloric acid is preferably dilute hydrochloric acid, and the present invention has no special limitation on the concentration of the dilute hydrochloric acid, and the type well known to those skilled in the art can be used.

[0046] In the present invention, deionized water is preferably used in the first water washing, the second water washing and the third water washing.

[0047] In the present invention, the first water washing, acetone washing, second water washing, hydrochloric acid washing, third water washing and ethanol washing are preferably carried out under ultrasonic conditions.

[0048] In the present invention, the drying temperature is preferably 50 to 70° C., and the drying time is preferably 10 to 20 hours.

[0049] In the present invention, the cleaning preferably includes water washing, ethanol soaking and water washing in sequence, and the time of the ethanol soaking is 5 to 10 minutes.

[0050] In the present invention, the sealing and standing time is preferably 4 to 10 hours.

[0051] In the present invention, cobalt nitrate, nickel nitrate, hexamethylenetetramine and water are preferably placed in an inner container of a reaction kettle and mixed evenly to obtain a metal precursor solution.

[0052] In the present invention, the cobalt nitrate and nickel nitrate in the metal precursor solution are preferably added in the form of cobalt nitrate hexahydrate and nickel nitrate hexahydrate, and the mass ratio of cobalt nitrate hexahydrate, nickel nitrate hexahydrate, hexamethylenetetramine and water in the metal precursor solution is preferably 0.2-0.4:0.7-1.2:1-1.3:30-50.

[0053] In the present invention, the water is preferably deionized water.

[0054] In the present invention, preferably 0.2-0.4 g of cobalt nitrate hexahydrate is weighed into a beaker, 0.7-1.2 g of nickel nitrate hexahydrate is weighed into a beaker, 1-1.3 g of hexamethylenetetramine is weighed into a beaker, and 30-50 mL of deionized water is added and stirred sufficiently to make the solution clear and transparent to obtain the metal precursor solution.

[0055] After obtaining the metal precursor solution, the present invention puts the ZIF-67@Ni foam into the metal precursor solution and uses a stainless steel shell to seal it for hydrothermal reaction, then takes it out and sequentially cleans and dries it to obtain the in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode.

[0056] In the present invention, the temperature of the hydrothermal reaction is preferably 80-100° C., and the time is preferably 0.5-3 h.

[0057] In the present invention, the hydrothermal reaction is preferably carried out in a hydrothermal reaction liner, and the filling degree of the hydrothermal reaction liner is preferably 60% to 80%.

[0058] The present invention has no particular limitation on the specific methods of cleaning and drying, and methods well known to those skilled in the art may be used.

[0059] The present invention also provides a nickel-cobalt double hydroxide nanosheet array electrode material prepared by the preparation method described in the above technical solution. The present invention firstly grows a ZIF-67 nanosheet array in situ on nickel foam by room temperature impregnation method, and then obtains a self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide (Ni-Co LDH) nanosheet array electrode by hydrothermal method. In the present invention, the nickel foam substrate acts as a conductive grid that promotes electron transfer; the electrode prepared by this method allows nitrogen-doped carbon to be self-compounded in a Ni-Co LDH matrix, and the excellent conductivity of the nitrogen-doped carbon can promote the charge transfer of the electrode during the energy storage process. The self-generated composite material has the characteristics of uniform symbiosis, interface stability, enhanced conductivity, etc.; in addition, the in-situ grown Ni-Co LDH nanosheet array not only inherits the sheet structure, porous characteristics and stability of ZIF-67, but also has excellent hydrophilicity, and a large number of sheet-like Ni-Co LDH are also grown on the nanosheet array structure, effectively avoiding the problems of stacking, agglomeration and low load of Ni-Co LDH; the electrode material prepared by this method can be directly used as an electrode without an adhesive, has a larger actual contact area with the electrolyte, better conductivity, is not easy to fall off during use, and has excellent electrochemical properties.

[0060] The present invention also provides the use of the nickel-cobalt double hydroxide nanosheet array electrode material described in the above technical solution in a supercapacitor.

[0061] The present invention has no particular limitation on the specific manner of the application, and any manner familiar to those skilled in the art may be used.

[0062] To further illustrate the present invention, the in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode provided by the present invention and its preparation method and application are described in detail below with reference to examples, but they should not be understood as limiting the scope of protection of the present invention.

[0063] Example 1

[0064] Step 1: Cut the nickel foam into 3*3cm size, and then put the nickel foam into beakers containing 50mL of deionized water, acetone, deionized water, dilute hydrochloric acid, deionized water, and ethanol for ultrasonic cleaning. The ultrasonic cleaning time is set to 10min, 15min, 10min, 10min, 10min, and 5min, respectively. After cleaning, transfer the nickel foam to a culture dish and put it into an oven and bake it at 60℃ for 12 hours.

[0065] Step 2: Weigh 1.2 g of cobalt nitrate hexahydrate into a beaker, then add 80 mL of deionized water and stir thoroughly to make the solution clear and transparent;

[0066] Step 3: Weigh 3 g of 2-methylimidazole into a beaker, then add 80 mL of deionized water and stir thoroughly to make the solution clear and transparent;

[0067] Step 4: Pour the solution prepared in step 2 into the solution prepared in step 3, add the nickel foam prepared in step 1 after sufficient stirring, and then seal the beaker and let it stand for 5 hours;

[0068] Step 5: Take out the product left to stand according to step 4, rinse the electrode surface with deionized water first, soak it in ethanol for 5 minutes after confirming that it is rinsed clean, then take it out and rinse it again with deionized water, finally transfer it to a culture dish and put it in an oven, and dry it at 60°C to prepare the ZIF-67@Ni foam material;

[0069] Step 6: Weigh 0.3 g of cobalt nitrate hexahydrate, 0.9 g of nickel nitrate hexahydrate, and 1.2 g of hexamethylenetetramine into a Teflon liner, then add 40 mL of deionized water and stir thoroughly to make the solution clear and transparent;

[0070] Step 7: Take out the dried product ZIF-67@Ni foam in step 5, put it into the solution obtained in step 6, use a stainless steel reactor shell to seal the Teflon liner, and then place the reactor in a 90°C oven for 0.5h;

[0071] Step 8: Take out the product prepared in step 7 and let it stand, rinse the electrode surface with deionized water, soak it in ethanol for 5 minutes after confirming that it is rinsed clean, then transfer it to a culture dish and put it in an oven, and dry it at 60°C to prepare an in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode;

[0072] Example 2

[0073] Step 1: Cut the nickel foam into 3*3cm size, and then put the nickel foam into beakers containing 50mL of deionized water, acetone, deionized water, dilute hydrochloric acid, deionized water, and ethanol for ultrasonic cleaning. The ultrasonic cleaning time is set to 10min, 15min, 10min, 10min, 10min, and 5min, respectively. After cleaning, transfer the nickel foam to a culture dish and put it into an oven and bake it at 60℃ for 12 hours.

[0074] Step 2: Weigh 1.2 g of cobalt nitrate hexahydrate into a beaker, then add 80 mL of deionized water and stir thoroughly to make the solution clear and transparent;

[0075] Step 3: Weigh 3 g of 2-methylimidazole into a beaker, then add 80 mL of deionized water and stir thoroughly to make the solution clear and transparent;

[0076] Step 4: Pour the solution prepared in step 2 into the solution prepared in step 3, add the nickel foam prepared in step 1 after sufficient stirring, and then seal the beaker and let it stand for 5 hours;

[0077] Step 5: Take out the product left to stand according to step 4, rinse the electrode surface with deionized water first, soak it in ethanol for 5 minutes after confirming that it is rinsed clean, then take it out and rinse it again with deionized water, finally transfer it to a culture dish and put it in an oven, and dry it at 60°C to prepare the ZIF-67@Ni foam material;

[0078] Step 6: Weigh 0.3 g of cobalt nitrate hexahydrate, 0.9 g of nickel nitrate hexahydrate, and 1.2 g of hexamethylenetetramine into a Teflon liner, then add 40 mL of deionized water and stir thoroughly to make the solution clear and transparent;

[0079] Step 7: Take out the dried product ZIF-67@Ni foam in step 5, put it into the solution obtained in step 6, use a stainless steel reactor shell to seal the Teflon liner, and then place the reactor in a 90°C oven for 1 hour;

[0080] Step 8: Take out the product prepared in step 7 and let it stand, rinse the electrode surface with deionized water, soak it in ethanol for 5 minutes after confirming that it is rinsed clean, then transfer it to a culture dish and put it in an oven, and dry it at 60°C to prepare an in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode;

[0081] Example 3

[0082] Step 1: Cut the nickel foam into 3*3cm size, and then put the nickel foam into beakers containing 50mL of deionized water, acetone, deionized water, dilute hydrochloric acid, deionized water, and ethanol for ultrasonic cleaning. The ultrasonic cleaning time is set to 10min, 15min, 10min, 10min, 10min, and 5min, respectively. After cleaning, transfer the nickel foam to a culture dish and put it into an oven and bake it at 60℃ for 12 hours.

[0083] Step 2: Weigh 1.2 g of cobalt nitrate hexahydrate into a beaker, then add 80 mL of deionized water and stir thoroughly to make the solution clear and transparent;

[0084] Step 3: Weigh 3 g of 2-methylimidazole into a beaker, then add 80 mL of deionized water and stir thoroughly to make the solution clear and transparent;

[0085] Step 4: Pour the solution prepared in step 2 into the solution prepared in step 3, add the nickel foam prepared in step 1 after sufficient stirring, and then seal the beaker and let it stand for 5 hours;

[0086] Step 5: Take out the product left to stand according to step 4, rinse the electrode surface with deionized water first, soak it in ethanol for 5 minutes after confirming that it is rinsed clean, then take it out and rinse it again with deionized water, finally transfer it to a culture dish and put it in an oven, and dry it at 60°C to prepare the ZIF-67@Ni foam material;

[0087] Step 6: Weigh 0.3 g of cobalt nitrate hexahydrate, 0.9 g of nickel nitrate hexahydrate, and 1.2 g of hexamethylenetetramine into a Teflon liner, then add 40 mL of deionized water and stir thoroughly to make the solution clear and transparent;

[0088] Step 7: Take out the dried product ZIF-67@Ni foam in step 5, put it into the solution obtained in step 6, use a stainless steel reactor shell to seal the Teflon liner, and then place the reactor in a 90°C oven for 2 hours;

[0089] Step 8: Take out the product of step 7 and let it stand, rinse the electrode surface with deionized water, soak it in ethanol for 5 minutes after confirming that it is rinsed clean, then transfer it to a culture dish and put it in an oven, and dry it at 60°C to prepare a nickel cobalt double hydroxide nanosheet array electrode material;

[0090] Example 4

[0091] Step 1: Cut the nickel foam into 3*3cm size, and then put the nickel foam into beakers containing 50mL of deionized water, acetone, deionized water, dilute hydrochloric acid, deionized water, and ethanol for ultrasonic cleaning. The ultrasonic cleaning time is set to 10min, 15min, 10min, 10min, 10min, and 5min, respectively. After cleaning, transfer the nickel foam to a culture dish and put it into an oven and bake it at 60℃ for 12 hours.

[0092] Step 2: Weigh 1.2 g of cobalt nitrate hexahydrate into a beaker, then add 80 mL of deionized water and stir thoroughly to make the solution clear and transparent;

[0093] Step 3: Weigh 3 g of 2-methylimidazole into a beaker, then add 80 mL of deionized water and stir thoroughly to make the solution clear and transparent;

[0094] Step 4: Pour the solution prepared in step 2 into the solution prepared in step 3, add the nickel foam prepared in step 1 after sufficient stirring, and then seal the beaker and let it stand for 5 hours;

[0095] Step 5: Take out the product left to stand according to step 4, rinse the electrode surface with deionized water first, soak it in ethanol for 5 minutes after confirming that it is rinsed clean, then take it out and rinse it again with deionized water, finally transfer it to a culture dish and put it in an oven, and dry it at 60°C to prepare the ZIF-67@Ni foam material;

[0096] Step 6: Weigh 0.3 g of cobalt nitrate hexahydrate, 0.9 g of nickel nitrate hexahydrate, and 1.2 g of hexamethylenetetramine into a Teflon liner, then add 40 mL of deionized water and stir thoroughly to make the solution clear and transparent;

[0097] Step 7: Take out the dried product ZIF-67@Ni foam in step 5, put it into the solution obtained in step 6, use a stainless steel reactor shell to seal the Teflon liner, and then place the reactor in a 90°C oven for 3 hours;

[0098] Step 8: Take out the product prepared in step 7 and let it stand, rinse the electrode surface with deionized water, soak it in ethanol for 5 minutes after confirming that it is rinsed clean, then transfer it to a culture dish and put it in an oven, and dry it at 60°C to prepare an in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode;

[0099] After the preparation is completed, the electrochemical performance of the in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode prepared in the embodiment is tested by the following method. The instruments and equipment required for the test include: an electrochemical workstation and a three-electrode system. The details are as follows:

[0100] Electrochemical performance test

[0101] The prepared electrode was installed into a three-electrode system and connected to an electrochemical workstation, and then its cyclic voltammetric characteristics and constant current charge-discharge characteristics were tested;

[0102] Electrochemical performance test of in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode:

[0103] Step a: Weigh 5.6 g of potassium hydroxide into a beaker, then add 50 mL of deionized water and stir thoroughly to make the solution clear and transparent;

[0104] Step b: Pour the solution prepared in step a into a clean electrolytic cell, and then install the counter electrode platinum sheet (1.5×1.5 cm) and the reference electrode Hg / HgO of the electrolytic cell;

[0105] Step c: installing the working electrode in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode material;

[0106] Step d: Connect the three-electrode system to an electrochemical workstation to test the electrochemical performance of the electrodes;

[0107] Figure 1 This is a scanning electron microscope image of the nickel-cobalt double hydroxide nanosheet array electrode material prepared in Example 2. Figure 1 It can be seen that this method successfully prepared electrode materials with nanosheet array structures, and the nanosheet materials grew uniformly and regularly without agglomeration or stacking.

[0108] Figure 2 This is the Fourier infrared absorption spectrum of the in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode prepared in Example 2. Figure 2 It can be seen that the in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode in the figure has a peak at 3681-3324 cm -1 Corresponding to OH, MO-H (M is Ni / Co), 610cm -1 、506cm -1 Corresponding to MO-H, proving the existence of nickel-cobalt double hydroxide; 2863cm -1 (CH), 1617cm -1 (C=N), 1332cm -1 (C=C), 991cm -1 The infrared absorption at (CN) indicates that nitrogen-doped carbon and nickel-cobalt double hydroxide have successfully achieved self-reintegration; while 1196cm -1 The infrared absorption at may be the carbonate generated during the hydrothermal process.

[0109] Figure 3 The cyclic voltammetry curves of the nickel-cobalt double hydroxide nanosheet array electrode materials prepared in Examples 1 to 4 are shown in FIG. Figure 3 It can be seen that within the hydrothermal time range of 0.5 to 3 hours, the electrode prepared under 1 hour hydrothermal conditions exhibits the best capacitive performance.

[0110] Figure 4 The cyclic voltammetry curve of the topological electrode material prepared in Example 2 is shown in FIG. Figure 4 It can be seen that in the range of 1 to 10 mV / s, the integrated area of ​​the CV curve increases with the increase of the scan rate, showing high-rate performance.

[0111] Figure 5 The constant current charge-discharge curve of the topological electrode material prepared in Example 2 is shown in FIG. Figure 5 It can be seen that the electrodes show almost symmetrical charge and discharge curves at different current densities, indicating that there is a highly reversible redox reaction between the electrode material and the electrolyte. Especially at a current density of 1A / g, the specific capacitance of the electrode is calculated to be 2985F / g.

[0112] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing an in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode, characterized in that: The following steps are involved: Mixing cobalt nitrate, 2-methylimidazole and water to obtain a mixed solution; The nickel foam is immersed in the mixed solution, sealed and allowed to stand, and then washed and dried in sequence to obtain a ZIF-67@Nifoam electrode; mixing cobalt nitrate, nickel nitrate, hexamethylenetetramine and water to obtain a metal precursor solution; The ZIF-67@Ni foam is placed in the metal precursor solution for hydrothermal reaction to obtain the in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode; the temperature of the hydrothermal reaction is 80-100° C. and the time is 0.5-3 h; The cobalt nitrate in the mixed solution is added in the form of cobalt nitrate hexahydrate, and the mass ratio of the nickel foam, cobalt nitrate hexahydrate, 2-methylimidazole and water in the mixed solution is 0.7-1:5-8:11-14:70-90; The cobalt nitrate and nickel nitrate in the metal precursor solution are added in the form of cobalt nitrate hexahydrate and nickel nitrate hexahydrate, and the mass ratio of cobalt nitrate hexahydrate, nickel nitrate hexahydrate, hexamethylenetetramine and water in the metal precursor solution is 0.2-0.4:0.7-1.2:1-1.3:30-50.

2. The preparation method according to claim 1, characterized in that: The nickel foam also includes pretreatment before use, and the pretreatment is a first water washing, acetone washing, a second water washing, hydrochloric acid washing, a third water washing, ethanol washing, and drying performed in sequence. The first water washing time is 10 to 20 minutes, the acetone washing time is 10 to 20 minutes, the second water washing time is 10 to 20 minutes, the hydrochloric acid washing time is 5 to 15 minutes, the third water washing time is 10 to 20 minutes, and the ethanol washing time is 10 to 20 minutes.

3. The preparation method according to claim 1, characterized in that: The drying temperature is 50-70° C. and the drying time is 10-20 hours.

4. The preparation method according to claim 1, characterized in that: The cleaning comprises water washing, ethanol soaking and water washing in sequence, and the ethanol soaking time is 5 to 10 minutes.

5. An in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the in-situ self-generated composite nitrogen-doped carbon and nickel-cobalt double hydroxide nanosheet array electrode as claimed in claim 5 in a supercapacitor.

Citation Information

Patent Citations

  • Ni-Co double metal hydroxide nanometer sheet / N-doped carbon fiber hybrid material and preparation method thereof

    CN105513819A

  • Porous Co3O4@Ni-MOF core-shell structure nanosheet array material and preparation method and application thereof

    CN112670093A